Design of soy protein/peptide-based colloidal particles and their role in controlling the lipid digestion of emulsions. (February 2022) - Shen, Penghui; Zhao, Mouming; Zhou, Feibai
Graphical abstract: Highlights: Soy protein is an excellent material in engineering interfaces to control lipolysis. Greener way calls for fabrication of soy protein-based colloidal particles (SPP). SPP including the hybrids could act as efficient Pickering-like stabilizers. SPP could form shared, unshared or gelled interfaces to modulate lipolysis. Insights into design of SPP-based interface provide potential for weight management. Abstract : The over consumption of lipid largely induces the serious obesity problem around the globe. In food products, the vast majority of lipids are present as emulsions wherein the modulation of lipolysis is significant for controlling energy intake. As one of the most commercialized proteins, soy protein inherently owns superior capacity in delaying lipolysis as emulsifier, and its capacity could be remarkably augmented once reconstructed as Pickering-like stabilizers. This mini review concisely summarized the recent advances in the fabrication of soy protein/peptide-based particles with varied physicochemical features, and their performance in controlling lipid digestion in emulsions as well as the mechanism involved was discussed with emphasis, aiming to provide certain guidance for the design of emulsion-based functional foods modulating lipid digestibility.